The Validity of Electronic Signatures in Electronic Transactions From The Perspective of Regulation Number 71 of 2019 - Rudolf Hitler Satriawan Sitorus; George Frans Wanma (Eduvest - Journal of Universal Studies, 2024)
The development of information and communication technology (ICT) has driven the rapid growth of electronic transactions. The use of electronic signatures (TTE) is also a practical solution in electronic transactions. This research aims to determine the validity of TTE in electronic transactions based on PP No. 71 of 2019. This research uses normative legal research methods with a juridical-normative approach. Research data was obtained from literature studies of statutory regulations, books, scientific journals and other secondary legal sources. Data were analyzed qualitatively using interpretation and description methods. The research results show that based on Government Regulation (PP) no. 71 of 2019 concerning Implementation of Electronic Systems and Transactions, electronic signatures are recognized as a valid form of signature in electronic transactions. Electronic Signatures used in Electronic Transactions can be generated through various signing procedures. Electronic Signatures have legal force and legal consequences as long as they meet the requirements. So it can be concluded that electronic signatures have validity and legal force that is recognized in electronic transactions.